Malaysian’s Young Consumer Preferences of Hijab - Fikry, Amily; Ahmad, Mohd Rozi (Journal of Reviews on Global Economics, 2019)
Researchers have long been interested in understanding young consumers’ purchasing behaviour, especially in terms of their purchasing preferences and decision-making styles. Zooming to hijab preferences, different angles of hijab have been studied. Out of 32.4 million of total population, Islam is the most widely professed religion in Malaysia. Thus, this research aims to obtain young consumer preferences of hijab. It was conducted through focus group interviews in one of the public university located in Selangor, Malaysia. The focus group interviews were audio taped and transcribed. There were 13 Malaysian female respondents; students of aged 20 to 25 years old. The findings thus far revealed that young consumer’s selection of hijab to wear and attend lectures is highly influenced by easiness to wear hijab, boost confidence as well as their moods and face shape. These factors make them feel more comfortable to move around with their active lifestyle as university students. Limitations and recommendations for future studies are discussed.